The collected works of Florence Nightingale / 13 Florence Nightingale : extending nursing / Lynn McDonald, editor - Nightingale, Florence (The collected works of Florence Nightingale, 2009)
Dramatis Personae -- Florence Nightingale: A Precis of Her Life -- Introduction to Volume 13 -- Key to Editing -- Extending Nightingale Nursing in Hospitals -- Nursing in Workhouse Infirmaries -- District Nursing -- Appendix A. Biographical Sketches